Theory of Time-dependent Space-charge-limited Conduction - CHAN, HO-KEI (IEEE, 2007)
We have developed a theory of timedependent space-charge-limited conduction in recent years to understand a hysteresis-shift phenomenon of graded ferroelectric films. The theory is a generalization of the conventional steady-state space-charge-limited conduction model to include (i) two carrier types (ptype and n-type), (ii) intrinsic conductivity and (iii) time dependence. Later, the theory was also applied to understand the hysteresis behaviour of homogeneous ferroelectric films. In this paper, a full and updated version of the theory is presented. At the limit of zero intrinsic conductivity, the theory implies the dominance of either carrier type. Accordingly, the independent assumptions of (i) a single carrier type and (ii) a negligible intrinsic conductivity in the conventional steady-state conduction model are interrelated.
Proceedings of the 9th IEEE International Conference on Solid Dielectrics
9th IEEE International Conference on Solid Dielectrics
PUBLISHED
Winchester, U. K.
This paper presents an updated version of the time-dependent space-charge-limited conduction model that was originally developed for the study of polarization offsets in compositionally graded ferroelectric films. It provides a more comprehensive justification of the mass-action approximation which is the cornerstone of the model.
Keywords: Physics